Comparison of pain intensity, smooth muscle cells density, and alpha-smooth muscle actin expression in ovarian and peritoneal endometriosis - Sutrisno, Sutrisno; Nooryanto, Muhammad; Gani, Shella Widya (Majalah Obstetri & Ginekologi, 2021)
HIGHLIGHT 1. Pain intensity, smooth muscle cells density, and alpha-SMA expression can be used to analyze the role of smooth muscle in endometriosis. 2. Compared to healthy individuals, those with endometriosis have higher pain intensity, smooth muscle cells density, and alpha-SMA expression. 3. Among endometriotic patients, those with peritoneal endometriosis have higher pain intensity, smooth muscle cells density, and alpha-SMA expression than those with ovarian endometriosis. 4. The expression of alpha-SMA, smooth muscle density, and pain intensity were found to correlate significantly in endometriosis. ABSTRACT Objectives: to identify the role of smooth muscle through the analysis of smooth muscle cells density, expression of a-SMA, and pain intensity. Materials and Methods: The study design was cross-sectional analytic observational. Study sample consisted of women with ovarian endometrios and women with peritoneal endometriosis who underwent laparoscopy and laparotomy in Dr. Saiful Anwar Hospital and RSIA Melati Hospital, both in Malang, Indonesia, from January until December 2019. There were 16 samples: 8 samples of ovarian endometriosis and 8 samples of peritoneal endometriosis. Smooth muscle cell density was analyzed by comparing the number of smooth muscle cells with the total area of endometriosis tissue in one microscopical field. a-SMA expression was obtained by immunohistochemistry. The degree of pain was determined by filling the part 1 point 1-11 of EHP-30 queistionnaire the day after the procedure. Data were analyzed with Independent T-test and Pearson's correlation test. Results: Pain intensity, smooth muscle cells density, and a-SMA expression was higher in endometriosis patients compared to healthy individuals. Pain intensity, smooth muscle cells density, and a-SMA expression was lower in the ovarian endometriosis compared to peritoneal endometriosis. Conclusion: There was a significant correlation between the expression of a-SMA, smooth muscle density, and pain intensity in endometriosis.